Mixed flavonoid supplementation attenuates postexercise plasma levels of 4-hydroxynonenal and protein carbonyls in endurance athletes - Nieman, D. C.; Valacchi, G.; Wentz, L. M.; Ferrara, F.; Pecorelli, A.; Woodby, B.; Sakaguchi, C. A.; Simonson, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
This double-blinded, placebo controlled, randomized crossover trial investigated the influence of 2-week mixed flavonoid versus placebo supplementation on oxinflammation markers after a 75-km cycling time trial in 22 cyclists (42.3 ± 1.7 years). Blood samples were collected before and after the 2-week supplementation, and then 0 hr, 1.5 hr, and 21 hr post 75-km cycling (176 ± 5.4 min, 73.4 ± .0% maximal oxygen consumption). The supplement provided 678-mg flavonoids with quercetin (200 mg), green tea catechins (368 mg, 180-mg epigallocatechin gallate), and anthocyanins (128 mg) from bilberry extract, with caffeine, vitamin C, and omega-3 fatty acids added as adjuvants. Blood samples were analyzed for blood leukocyte counts, oxinflammation biomarkers, including 4-hydroxynonenal, protein carbonyls, and peripheral blood mononuclear mRNA expression for cyclooxygenease-2 and glutathione peroxidase. Each of the blood biomarkers was elevated postexercise (time effects, all ps < .01), with lower plasma levels for 4-hydroxynonenal (at 21-hr postexercise) in flavonoid versus placebo (interaction effect, p = .008). Although elevated postexercise, no trial differences for the neutrophil/lymphocyte ratio (p = .539) or peripheral blood mononuclear mRNA expression for cyclooxygenease-2 (p = .322) or glutathione peroxidase (p = .839) were shown. Flavonoid supplementation prior to intensive exercise decreased plasma peroxidation and oxidative damage, as determined by 4-hydroxynonenal. Postexercise increases were similar between the flavonoid and placebo trials for peripheral blood mononuclear mRNA expression for cyclooxygenease-2 and the nuclear factor erythroid 2-related factor 2 related gene glutathione peroxidase (NFE2L2). The data support the strategy of flavonoid supplementation to mitigate postexercise oxidative stress in endurance athletes.